If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -9 = 6x + 7 Reorder the terms: -9 + 6x = 6x + 7 Reorder the terms: -9 + 6x = 7 + 6x Add '-6x' to each side of the equation. -9 + 6x + -6x = 7 + 6x + -6x Combine like terms: 6x + -6x = 0 -9 + 0 = 7 + 6x + -6x -9 = 7 + 6x + -6x Combine like terms: 6x + -6x = 0 -9 = 7 + 0 -9 = 7 Solving -9 = 7 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| x=y^2+6y+89 | | H=-16t^2+224t+240 | | 3(x-4)=-4x+36 | | (x+5)-2(4x-1)=0+2 | | -6(w+4)=-2w-28 | | 55x-36= | | 5.6(x-2)=-0.4x+19.6 | | x^2+3x+6x= | | (19b-7)-6(3b+1)=-2 | | (9.3+0.7)(4.4-0.6)= | | 30=5(d-2) | | 2.4/.7 | | 6ln(x-9)=1 | | 59-w=208 | | 6t-8=4t-4 | | 9x/-3x-5 | | 3y+12=8y-20 | | (7x+8)(4x-7)=0 | | (2x+5)(2x+5)=4x^2+20x+25 | | 4(5/3-3/2y)-9y=9 | | 5(2)+4y=-7 | | 5(-4)+4y=-7 | | 2x=5+y | | 8x?=4/6 | | 5(1)+4y=-7 | | 18x+12=9x+6 | | 5(-3)+4y=-7 | | 3z+6=8z-46 | | X-5=6.25 | | -.06x=-1.2 | | 8m-10=-74 | | 7s+4g=18.89 |